THEORETICAL ASPECTS OF ADAPTABILITY IN MODERN CONDITIONS OF BUSINESS’ ACTIVITIES (INNOVATIVE ECONOMY, 2020)
Klymenko S.M., Shevchuk N.V. THEORETICAL ASPECTS OF ADAPTABILITY IN MODERN CONDITIONS OF BUSINESS’ ACTIVITIESPurpose. The aim of the article is the development theoretical and methodical aspects of determining the adaptability of enterprises in terms of conformity with the future vision and to reason the author's approach to its research in the attributive and consequential aspects.Methodology of research. The general scientific and special methods of scientific knowledge are used here due to the aim of this work. The following methods were used for the research: bibliographic and terminological analysis - to determine the author's interpretation of the content of enterprise adaptability; scientific generalization - when systematizing modern approaches to the assessment of enterprise adaptability; system analysis and synthesis - when substantiating the attributive and results aspects of the perspective approach to the definition of enterprise adaptability.Findings. It is determined that understanding of adaptability as the organizational capacity of enterprises to timely and adequately respond to changes in the environment has shifted the research focus to modern strategic issues. The appropriateness of a holistic approach to the definition of adaptability, not only as a consequence of the adoption and implementation of past management decisions (retrospective aspect), but also from the point of view of the availability and conformity of the internal system characteristics of the business to the vision of the future (perspective aspect), has been reasoned. The logic of definition of adaptability as a set of attributive and results aspects, which reveals its content in the categories of scenario theory, is substantiated and formalized.Originality. The scientific novelty of the research results is in launching a new direction of adaptive research in line with the strategic vision of the future. In this aspect, the provision of adaptability is based on the structuring of uncertainty and complexity of the external environment, its prediction, which allows identifying, assessing and transforming the environment into resources. Effective use of them will help to achieve the desired and expected economic outcomes.Practical value. A fundamentally new logic for ensuring the adaptability of modern business structures, taking into account the post-industrial challenges of the environment, has been formed.Key words: adaptability; scenarios; vision of the future; strategy.
Keywords: Key words; adaptability; scenarios; vision of the future; strategy.